Sustained response in early responders to safinamide in patients with Parkinson's disease and motor fluctuations: A post hoc analysis of the SETTLE study - Bhidayasiri, Roongroj; Koebis, Michinori; Kamei, Takanori; Ishida, Takayuki; Suzuki, Ippei; Cho, Jin Whan; Wu, Shey-Lin (Frontiers in Neurology, 2023)
Safinamide is a selective, reversible, monoamine oxidase B inhibitor for the treatment of patients with Parkinson’s disease (PD) and motor fluctuations. This was a post hoc analysis of the SETTLE study, in which patients with PD and motor fluctuations were randomly assigned to 24-week treatment with safinamide (50 mg/day for 2 weeks, increased to 100 mg/day if tolerated) or placebo. In the present analysis, responders were defined according to their treatment responses at Week 2 and Week 24 based on changes in ON-time without troublesome dyskinesia from baseline with cutoffs of 1 hour. It was found that 81% (103/127) of the responders at Week 2 maintained the response through Week 24 in the safinamide group. Other outcomes did not necessarily coincide with the ON-time response; however, “Early” responders who showed a treatment response at both Week 2 and Week 24 had substantial improvements from baseline in OFF-time, UPDRS Part II and III scores, and PDQ-39 summary index scores through Week 24. The safinamide group had a higher proportion of early responders than the placebo group (39% vs 20%, p < 0.0001). At baseline, early responders in the safinamide group had significantly higher UPDRS Part II and III scores, shorter ON-time, and longer OFF-time than the other responder populations. In conclusion, the results of the present post hoc analysis suggest that patients with a short ON-time, severe motor symptoms, and highly compromised activities of daily living can benefit from safinamide early in treatment and over the long term.